The Effect of Financial Literacy on Malang District Society’s Financial Behavior - Novita Ratna Satiti; Chalimatuz Sa'diyah (Universitas Trisakti, 2020)
This study aims to analyze the effect of financial literacy on financial behavior in the community in Malang district. The design and approach used is the mix method. The data used in this study are primary in the form of literacy and financial behavior of the public, and secondary data in the form of financial institution information in the Malang Regency. Samples of farmers in 33 districts were selected using Multi Stage Random Sampling. Data was collected by observing, interviewing and distributing questionnaires. The result showed that the interaction between financial literacy and finance house significantly affects financial behavior. Financial literacy is to have the ability and knowledge of concept and risk, and skill to make more effective decision in finance individually, in a family, and in society. The finance house would help the society to know how to come into decision in managing their finance. It would change the society’s behavior from having lack of knowledge, ability, and belief in financial products and services to having them comprehensively, including knowing features, risks, and advantages of financial products and services. Additionally, it is expected that the society would have ability in using the financial products and services.